Manufacture of desired end products by means of fine treatment of coal tar resin; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 2 - Lozbin V. I.; Mochalnikov S. V.; Solodov G. А.; Nevedrov А. V.; Papin А. V. (Chemistry, 2007)
Заглавие с титульного листа